Hydropower Development in Nepal: Achievements and Opportunities - Pandey, Lekha Nath; Patodiya, Pawan Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article has assessed the progress and opportunities within hydropower sector of Nepal. It has emphasized its pivotal role in shaping the economic future the country. Hydropower has been integral to the development of Nepal, with its journey beginning over a century ago. Despite challenges such as political instability, limited infrastructure, and financing difficulties, significant achievements have been made. The study highlights opportunities for further growth, particularly in large-scale and multi-purpose hydropower projects. The article has explored the roles of government, the private sector, and international cooperation in driving sustainable hydropower development. It has given some recommendations to overcome challenges and maximize future opportunities. Emphasizing environmental and social considerations, the study suggests that hydropower will continue to be central to the economic ambitions and its transition to a greener, more resilient energy future of Nepal.